Plasmonic random laser enabled artefact-free wide-field fluorescence bioimaging: uncovering finer cellular features. Issue 10 (11th April 2022) - Gayathri, R.; Suchand Sandeep, C. S.; Gummaluri, V. S.; Asik, R. Mohamed; Padmanabhan, Parasuraman; Gulyás, Balázs; Vijayan, C.; Murukeshan, V. M.
Abstract : An artefact-free, wide-field fluorescence bioimaging modality based on spatially incoherent plasmonic random laser is proposed and demonstrated for the first time for high contrast in vivo bioimaging. Abstract : Narrow bandwidth, high brightness, and spectral tunability are the unique properties of lasers that make them extremely desirable for fluorescence imaging applications. However, due to the high spatial coherence, conventional lasers are often incompatible for wide-field fluorescence imaging. The presence of parasitic artefacts under coherent illumination causes uneven excitation of fluorophores, which has a critical impact on the reliability, resolution, and efficiency of fluorescence imaging. Here, we demonstrate artefact-free wide-field fluorescence imaging with a bright and low threshold silver nanorod based plasmonic random laser, offering the capability to image finer cellular features with sub-micrometer resolution even in highly diffusive biological samples. A spatial resolution of 454 nm and up to 23% enhancement in the image contrast in comparison to conventional laser illumination are attained. Based on the results presented in this paper, random lasers, with their laser-like properties and spatial incoherence are envisioned to be the next-generation sources for developing highly efficient wide-field fluorescence imaging systems having high spatial and temporal resolution for real-time, in vivo bioimaging.